Knowledge banking in global education policy: A bibliometric analysis of World Bank publications on public-private partnerships - Menashy, Francine; Read, Robyn (Education Policy Analysis Archives, 2016)
As a leading mobilizer of international development and educational knowledge, the World Bank has been critiqued in two key areas: (1) the dominance of economic thinking in its policies, and (2) its Northern-generated knowledge which informs its work in the Global South. In this paper, we investigate the disciplinary foundation of Bank knowledge, as well as its geographic representation. This study pays particular attention to knowledge mobilization relating to one of the most contentious policy prescriptions worldwide, and one that the Bank has historically supported: private sector engagement in education. By employing the concepts of economic imperialism and policy networks to frame our study, and through the use of a bibliometric methodological approach, we trace the authorship patterns of publications cited in a series of key World Bank documents on private sector engagement in education. Our findings show that the World Bank mobilizes research production from the Global North, which reflects a disproportionate economic disciplinary focus. Moreover, through a mapping of the cited authors, this network is shown to be highly narrow and privileges authors from a small subset of elite institutions.